O atendimento anti-rábico humano em Minas Gerais, de 1999-2004 - Valeria de Melo Rodrigues e Oliveira (2005)
With the reduction of cases of human rabies transmitted by dogs in Brazil, the evaluation of anti-rabies human care becomes a necessity of the service, given the lack of correlation between aggression, treatment indication and local epidemiological situation. The aim of this study was to describe and evaluate some aspects of human anti-rabies treatment in Minas Gerais, from 1999 to 2004. We conducted a descriptive retrospective observational study, correlating areas of risk for human rabies transmitted by dogs and the information registered in various information systems of SUS-MG. Shape evaluated 132,452 records from the National Notifiable Diseases - SINAN, and 339,012 service records made by the Superintendent of Epidemiology Zoonoses Health Secretariat of Minas Gerais. There was an indication that treatment is excessive in areas of high and low risk, since most attacks are made by healthy dogs, unlike the high-risk areas, where there was a decrease in the treatment indication. Information systems have involved isolated bases, not acting as a network. There is still underreported by as much as quiet city by the poor quality of information. The surveillance aspect of the event is a multicenter, but the interfaces do not communicate, creating insecurity to the attending physician to indicate only the observation of animal abuser